Analysis of Modelling Frameworks for Knowledge Acquisition - Thirunavukkarasu, Thirunavukkarasu K; Ashu, Abhilash; Singh, Digvijay; Khan, Shahnawaz S (International Journal of Computer Sciences and Engineering, 2025)
Knowledge acquisition is an elementary stage of knowledge engineering. The process includes extracting the raw data from various sources that are later structured and organized in such a form that contribute in providing knowledge. Usually knowledge can be acquired from sources such as primer, manuals and simulation models but a highly elaborate acquisition comes from human experts. This paper projects the various modelling techniques and framework. The proposed Knowledge Acquisition Framework(KAF)emphasizes on the models like Common KADS, MIKE, PROTEGE and their concept of knowledge acquisition. This technology helps in the process of building and framing various application of knowledge engineering